Let-A-a-b-c-d-Find-a-condition-on-a-b-c-d-so-that-A-n-1-A-n-nA-n-N-A-n-1-A-n-nA-A-n-A-n-1-n-1-A-A-n-1-A-n-2-n-2-A-A-n-2-A-n-3-n-3-A-A-4-A-3-3A-A-3-A-2-2A

Question Number 3566 by Yozzii last updated on 15/Dec/15
$${Let}\:{A}=\begin{pmatrix}{{a}}&{{b}}\\{{c}}&{{d}}\end{pmatrix}.\:{Find}\:{a}\:{condition}\:{on} \\$$$${a},{b},{c},{d}\:{so}\:{that}\:{A}^{{n}+\mathrm{1}} −{A}^{{n}} ={nA},\:{n}\in\mathbb{N}. \\$$$$\\$$$${A}^{{n}+\mathrm{1}} −{A}^{{n}} ={nA} \\$$$${A}^{{n}} −{A}^{{n}−\mathrm{1}} =\left({n}−\mathrm{1}\right){A} \\$$$${A}^{{n}−\mathrm{1}} −{A}^{{n}−\mathrm{2}} =\left({n}−\mathrm{2}\right){A} \\$$$${A}^{{n}−\mathrm{2}} −{A}^{{n}−\mathrm{3}} =\left({n}−\mathrm{3}\right){A} \\$$$$… \\$$$${A}^{\mathrm{4}} −{A}^{\mathrm{3}} =\mathrm{3}{A} \\$$$${A}^{\mathrm{3}} −{A}^{\mathrm{2}} =\mathrm{2}{A} \\$$$${A}^{\mathrm{2}} −{A}={A} \\$$$$\\$$$$\:{So},\:{A}^{{n}+\mathrm{1}} −{A}=\left({n}+{n}−\mathrm{1}+{n}−\mathrm{2}+…+\mathrm{3}+\mathrm{2}+\mathrm{1}\right){A} \\$$$${A}^{{n}+\mathrm{1}} ={A}+\frac{{n}\left({n}+\mathrm{1}\right)}{\mathrm{2}}{A} \\$$$${A}^{{n}+\mathrm{1}} =\frac{{n}^{\mathrm{2}} +{n}+\mathrm{2}}{\mathrm{2}}{A} \\$$$${A}^{{n}} =\frac{\left({n}−\mathrm{1}\right)^{\mathrm{2}} +{n}+\mathrm{1}}{\mathrm{2}}{A} \\$$$${A}^{{n}} =\frac{{n}^{\mathrm{2}} −{n}+\mathrm{2}}{\mathrm{2}}{A}\:\:\left({n}\geqslant\mathrm{1}\right),\:{A}=\begin{pmatrix}{{a}}&{{b}}\\{{c}}&{{d}}\end{pmatrix}\:. \\$$$$\\$$$$\\$$$$\\$$
Commented by prakash jain last updated on 15/Dec/15
$${A}^{\mathrm{2}} =\begin{pmatrix}{{a}^{\mathrm{2}} +{bc}}&{{ab}+{bd}}\\{{ac}+{cd}}&{{bc}+{d}^{\mathrm{2}} }\end{pmatrix}\:=\begin{pmatrix}{\mathrm{2}{a}}&{\mathrm{2}{b}}\\{\mathrm{2}{c}}&{\mathrm{2}{d}}\end{pmatrix} \\$$$${a}^{\mathrm{2}} +{bc}=\mathrm{2}{a}\:\:\:\left(\mathrm{1}\right) \\$$$${ab}+{bd}=\mathrm{2}{b}\:\:\:\left(\mathrm{2}\right) \\$$$${ac}+{cd}=\mathrm{2}{c}\:\:\:\left(\mathrm{3}\right) \\$$$${bc}+{d}^{\mathrm{2}} =\mathrm{2}{d}\:\:\:\left(\mathrm{4}\right) \\$$$$\mathrm{4}\:{variables}\:{and}\:\mathrm{4}\:{equation} \\$$$${from}\:\left(\mathrm{1}\right)\:{and}\:\left(\mathrm{4}\right) \\$$$${a}^{\mathrm{2}} −{d}^{\mathrm{2}} =\mathrm{2}\left({a}−{d}\right)\Rightarrow{a}={d}\:{or}\:{a}+{d}=\mathrm{2} \\$$$${case}\:\mathrm{1}\:{a}={d} \\$$$${from}\:\left(\mathrm{2}\right)\:{db}+{bd}=\mathrm{2}{b}\Rightarrow{b}=\mathrm{0}\:{or}\:{d}=\mathrm{1} \\$$$$\:\:\:\:\:\:\:\mathrm{1}{a}.\:{case}\:{b}=\mathrm{0} \\$$$$\:\:\:\:\:\:\:\:{from}\:\left(\mathrm{4}\right)\:{d}^{\mathrm{2}} =\mathrm{2}{d}\Rightarrow{d}=\mathrm{0}\:{or}\:{d}=\mathrm{2} \\$$$$\:\:\:\:\:\:\:\:\:\:\:\:\mathrm{1}{aa}\centerdot\:\mathrm{case}\:{d}=\mathrm{0} \\$$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:{a}={b}={c}={d}=\mathrm{0}\:\:\:….\left({A}\right) \\$$$$\:\:\:\:\:\:\:\:\:\:\:\:\mathrm{1}{ab}.\:{csse}\:{d}=\mathrm{2} \\$$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:{a}={d}=\mathrm{2} \\$$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:{ac}+{dc}=\mathrm{2}{c}\Rightarrow\mathrm{2}\sqrt{\mathrm{2}}{c}=\mathrm{2}{c}\Rightarrow{c}=\mathrm{0} \\$$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:{a}={d}=\mathrm{2},\:{b}={c}=\mathrm{0}\:\:\:\:\left({B}\right) \\$$$$\:\:\:\:\:\:\:\:\mathrm{1}{b}.\:{case}\:{d}=\mathrm{1} \\$$$$\:\:\:\:\:\:\:\:\:\:\:\:\:{a}={d}=\mathrm{1},\:{bc}=\mathrm{1}\:\:\:…\left({C}\right) \\$$$${case}\:\mathrm{2}:\:{a}+{d}=\mathrm{2} \\$$$$\:\:\:\:{b},\:{c}\:{can}\:{take}\:{any}\:{vale}\:\left({D}\right) \\$$$$\mathrm{To}\:\mathrm{satiafy}\:{A}^{\mathrm{2}} =\mathrm{2}{A}\:\mathrm{solution}\:\mathrm{are} \\$$$$\left({S}\mathrm{ol}\:{A}\right)\:{a}={b}={c}={d}=\mathrm{0}\:{th}\mathrm{is}\:\mathrm{satisifies}\:\mathrm{genral}\:\mathrm{condtion} \\$$$$\left(\mathrm{Sol}\:\mathrm{B}\right)\:{a}={d}=\mathrm{2},\:{b}={c}=\mathrm{0} \\$$$$\:\:\:\:\:\:{to}\:{be}\:{checked}\:{for}\:{higher}\:{powers}. \\$$$$\left(\mathrm{Sol}\:\mathrm{C}\right)\:{a}={d}=\mathrm{1},\:{cb}=\mathrm{1} \\$$$$\:\:\:\:\:\:{to}\:{be}\:{checked}\:{for}\:{higher}\:{powers}. \\$$$$\left(\mathrm{Sol}\:\mathrm{D}\right)\:{b},{c}\:{a},\:{d}=\mathrm{1}−{a} \\$$$$\:\:\:\:\:{to}\:{be}\:{checked}\:{for}\:{higher}\:{powers}. \\$$$$\mathrm{Continue} \\$$
Answered by prakash jain last updated on 15/Dec/15
$${A}=\begin{pmatrix}{\mathrm{2}}&{\mathrm{0}}\\{\mathrm{0}}&{\mathrm{2}}\end{pmatrix}\:{A}^{\mathrm{2}} =\begin{pmatrix}{\mathrm{4}}&{\mathrm{0}}\\{\mathrm{0}}&{\mathrm{4}}\end{pmatrix}\:{A}^{{n}} =\begin{pmatrix}{\mathrm{2}^{{n}} }&{\mathrm{0}}\\{\mathrm{0}}&{\mathrm{2}^{{n}} }\end{pmatrix} \\$$$${does}\:{not}\:{satisfy}\:{general}\:{comdition}. \\$$$${so}\: \\$$$${a}={b}={c}={d}=\mathrm{0}\:{is}\:{solution} \\$$$${a}={d}=\mathrm{2},{b}={d}=\mathrm{0}\:{is}\:{not}\:{solution}. \\$$$${S}\mathrm{ol}\:\left(\mathrm{C}\right)\:\mathrm{and}\:\left(\mathrm{D}\right)\:\mathrm{to}\:\mathrm{be}\:\mathrm{checked}. \\$$
Answered by prakash jain last updated on 15/Dec/15
$$\mathrm{Actually}\:\mathrm{there}\:\mathrm{is}\:\mathrm{an}\:\mathrm{easier}\:\mathrm{way}. \\$$$${A}^{\mathrm{2}} =\mathrm{2}{A} \\$$$${A}^{\mathrm{3}} −{A}^{\mathrm{2}} =\mathrm{2}{A} \\$$$${A}^{\mathrm{3}} =\mathrm{4}{A} \\$$$${A}^{\mathrm{4}} −{A}^{\mathrm{3}} =\mathrm{3}{A} \\$$$${A}^{\mathrm{3}} \centerdot{A}−\mathrm{4}{A}=\mathrm{3}{A} \\$$$$\mathrm{4}{A}^{\mathrm{2}} −\mathrm{4}{A}=\mathrm{3}{A} \\$$$$\mathrm{8}{A}−\mathrm{4}{A}=\mathrm{3}{A} \\$$$$\Rightarrow{a}={b}={c}={d}=\mathrm{0} \\$$